Critical evaluation of vinflunine in the treatment of refractory metastatic urothelial carcinoma. - Morel, A; Talbot, D (Dove Medical Press Ltd., 2010)
Urothelial carcinoma (UC) accounts for 5% to 10% of malignancies in men in Europe and the United States. For locally advanced or metastatic disease, there are two standard firstline chemotherapy regimens: MVAC (methotrexate, vinblastine, doxorubicin, cisplatin) and gemcitabine/cisplatin. For refractory disease, there is currently no standard treatment. Vinflunine, a second-generation Vinca alkaloid, is the first chemotherapeutic agent to be evaluated in a large UC second-line population. This review discusses the pre-clinical and clinical data published, and compares vinflunine to alternative single agents and combination regimens tested in this setting. Based on the results of the phase II and III clinical trials, there appears to be sufficient evidence to support the use of vinflunine in the second-line setting.